2022
DOI: 10.58803/jclr.v1i1.66
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Empathy-enhancing Techniques on EFL Learners’ Empathy, Language Proficiency, and Perception of Classroom Activities

Abstract: Introduction: Learning English as a foreign language has been affected by new teaching approaches in the field of teaching. There is a keen in shift from studying teachers’ teaching to learners’ learning and learners' psychological and social factors. Therefore, the current study aimed to examine the impact of empathy- enhancing techniques on EFL learners’ language proficiency, perception of classroom activities, and empathy. Methodology: To do so, three main variables were measured among 60 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As for learners, Kianinezhad (2023) ran a study in Iran and discovered a positive relationship between teacher empathy and EFL students' classroom engagement. In the same context, Karimian (2022) conducted an experimental study on 60 EFL students and found a positive association between teacher empathy and students' empathy and language achievement, as shown in the experimental group. In a conceptual study, in China, Zhang (2022) provided a comprehensive guide on how teacher empathy can contribute to L2 learners' engagement.…”
Section: Previous Studiesmentioning
confidence: 92%
“…As for learners, Kianinezhad (2023) ran a study in Iran and discovered a positive relationship between teacher empathy and EFL students' classroom engagement. In the same context, Karimian (2022) conducted an experimental study on 60 EFL students and found a positive association between teacher empathy and students' empathy and language achievement, as shown in the experimental group. In a conceptual study, in China, Zhang (2022) provided a comprehensive guide on how teacher empathy can contribute to L2 learners' engagement.…”
Section: Previous Studiesmentioning
confidence: 92%